G130 E-therapies for mental health problems in children and young people: A systematic review and focus group investigation. (7th April 2014) - Loucas, C; Pennant, M; Whittington, C; Naqvi, S; Sealey, C; Stockton, S; Kelvin, R; Fonagy, P; Kendall, T
Abstract : Aims: To review the effectiveness of e-mediated therapies and computer applications for children and young people (CYP) with mental health (MH) problems. To conduct focus groups eliciting service users views on computer-based applications. This work is part of a DH-commissioned website which will provide e-learning to people assisting CYP with MH problems, overseen by the MindEd Consortium at RCPCH. Methods: Medical, psychological/sociological, educational and grey literature databases were searched for randomised controlled trials of interventions for MH problems in CYP, either through remote therapist contact (e-mediated therapy) or computer-based applications. Studies were included if the mean age of participants was <18 years or all participants were ≤25 years. In addition, two focus groups of young people aged ≤25 years used four computerised CBT (cCBT) programs for anxiety and/or depression followed by facilitated discussion. Results: The review included studies of e-mediated and computer-based therapies for anxiety and depression (N=26), phobia (N=2), OCD (N=2), PTSD (N=1), eating disorders (N=6), ADHD (N=10), conduct disorder (N=2), substance misuse (N=11), autism (N=1), Tourette syndrome (N=1) and psychosis (N=1). Based on the GRADE system, the evidence was predominantly low quality with limited data, inadequate study design and unreliable outcome measures being major contributors to downgrading. The strongest evidence was for cCBT programs for depression in adolescents, and there was some promise for cCBT programs for anxiety in adolescents. The focus groups identified several key issues, including: the need for products to be engaging and up-to-date; the desire to set own goals; being active in therapy; continued contact with therapists; and the importance of endorsement by professionals. Conclusions: Computer-based applications such as cCBT show promise and e-mediated strategies are potentially useful. In the provision and development of new products, input is needed from specialists in software design as well as psychology, with consideration given to the software's technological suitability, therapeutic benefit and acceptability, as well as individual autonomy and integration with MH services. There should be continued robust evaluation of the evidence for effectiveness and cost effectiveness.